ANALISIS PEMANFAATAN INTERNET SEBAGAI MEDIA PEMBELAJARAN SISWA PADA PELAJARAN PEMASARAN ONLINE KELAS X SMKN 3 - Marsela, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
ABSTRACT The problem in this research is the utilization of the Internet as a medium of learning by students on the subjects in class X Online Marketing Marketing Department of SMK Negeri 3 Pontianak. Source of the data that the class X as many as five people, Chairman of the Department as much as one person, and Online Marketing teacher as much as one person. Data collection techniques used in this study were (1) direct communication techniques with the tools interview, (2) direct observation techniques with the tools of observation guidelines, and techniques of documentary studies with the appliance documents. Technique of determining the credibility of the data there are 2 of triangulation and triangulation techniques. Data analysis technique consists of four, namely data collection, data reduction, data presentation, verification and conclusion. The findings are Utilization of the Internet as a medium of learning by students on the subjects in class X Online Marketing Department of Marketing SMK Negeri 3 Pontianak already done but not optimal. Keywords: Media learning and use of the Internet